2015
DOI: 10.1103/physrevstab.18.071304
|View full text |Cite
|
Sign up to set email alerts
|

Laser-driven high-energy proton beam with homogeneous spatial profile from a nanosphere target

Abstract: A high-energy, high-yield proton beam with a good homogeneous profile has been generated from a nanosphere target irradiated by a short (30-fs), intense (7 × 10 20 W=cm 2) laser pulse. A maximum proton energy of 30 MeV has been observed with a high proton number of 7 × 10 10 in the energy range 5-30 MeV. A homogeneous spatial profile with a uniformity (standard deviation from an average value within 85% beam area) of 15% is observed with the nanosphere dielectric target. Particle-in-cell simulations show the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 28 publications
6
42
0
Order By: Relevance
“…The enhanced energy absorption can be obtained also with other structure geometries, such as rectangles [17,21,27] or nanospheres [20,22]. Our model can, in principle, be extended to account for different structure geometries.…”
Section: Discussion On Other Target Featuresmentioning
confidence: 87%
See 2 more Smart Citations
“…The enhanced energy absorption can be obtained also with other structure geometries, such as rectangles [17,21,27] or nanospheres [20,22]. Our model can, in principle, be extended to account for different structure geometries.…”
Section: Discussion On Other Target Featuresmentioning
confidence: 87%
“…Different approaches such as varying the target thickness [8], nanostructuring the back surface of the target [9,10] or growing a layer of low density foam [11][12][13] have already been studied. Several publications have reported that adding periodic nanostructures on the target front surface enhances drastically the laser energy absorption [13][14][15][16][17][18][19][20][21]. This generates ions with much higher energies than the ones obtained when targets with a flat surface are used [13,[20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial modulations of the proton beams have been observed for insulator targets (e.g. plastic, CH) [14][15][16][17] and attributed to an instability of the ionization front that affects the uniformity of the sheath E-field [16].…”
mentioning
confidence: 99%
“…We combine the already‐established plasma‐assisted vapor‐phase deposition of PEO with the recently developed deposition of plasma‐polymerized acrylic acid NPs (ppAA NPs) . The advantage of this approach lies in the fact that ppAA NPs are produced in a separate vacuum chamber and are embedded into ppPEO as ready‐made entities. Therefore, the phase separation processes are not governed by the kinetic phenomena of macromolecular diffusion.…”
Section: Introductionmentioning
confidence: 99%